Students’ feedback literacy in higher education: an initial scale validation study - Woitt, Svenja; Weidlich, Joshua; Jivet, Ioana; Orhan Göksün, Derya; Drachsler, Hendrik; Kalz, Marco (Teaching in higher education, 2023)
Given the crucial role of feedback in supporting learning in higher education, understanding the factors influencing feedback effectiveness is imperative. Student feedback literacy, that is, the set of attitudes and abilities to make sense of and utilize feedback is therefore considered a key concept. Rigorous investigations of feedback literacy require psychometrically sound measurement. To this end, the present paper reports on the development and initial validation (N = 221) of a self-report instrument. Grounded in the conceptual literature and building on previous scale validation efforts, an initial overinclusive item pool is generated. Exploratory factor analysis and the Rasch measurement model yield adequate psychometric properties of an initial scale measuring two dimensions: feedback attitudes and feedback practices with a total of 21 items. We further provide evidence for criterion-related validity. Findings are discussed in light of the emerging feedback literacy literature and avenues for further improvement of the scale are reported.
Online veröffentlicht: 17. Okt. 2023
Early access
Gesehen am 31.01.2024